Penetapan Kadar Boraks Pada Makanan Yang Beredar Di Pasar Semarang Timur Menggunakan Metode Spektrofotometri UV-Vis - Christina, Odilia Dea; Mahesa, Sandi; Wirawati, Ninik (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2023)
Borax (Sodium tetraborate) is a dangerous preservative that is not permitted to be used as a food ingredient. Borax is often misused to preserve various foods such as meatballs, wet noodles, banana molen, dumplings, lontong, ketupat, dumplings. In large quantities borax causes fever, anuria, coma, central nervous system damage, cyanosis, kidney damage, anemia, vomiting, diarrhea. The aim of this research is to determine borax levels in frequently consumed foods circulating in the East Semarang market. The food samples studied were meatballs, wet noodles and crackers sold at the East Semarang Market. Qualitative sample testing is organoleptic testing and TLC. In quantitative testing by determining levels using UV-Vis spectrophotometry using ethanol solvent. A total of 3 meatball samples, 1 noodle sample contained Borax. The borax levels in the meatball samples were B1 0.0052%, B2 0.0045%, B3 0.0046%. And the borax content in the wet noodle sample was M3 0.0045%.